2016
DOI: 10.1097/eja.0000000000000534
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age on anaesthesiologists’ competence

Abstract: The international anaesthesia community is getting older, in line with trends worldwide, and as men and women age there is the risk that psychophysiological decline could have an impact on clinical practice. Impairment of technical and nontechnical skills could have a negative impact on patients' safety and outcomes. The ageing process may not necessarily go hand-in-hand with a predictable pattern of decreased competence as not all aspects of functional decline are affected at the same rate and to the same ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 69 publications
0
19
0
6
Order By: Relevance
“…Majority of the respondents (79.5%) were generally satisfied with their present life. The age distribution of physicians has changed substantially over the past three decades [1]. In 2010 in the United States and in 2012 in Canada, 39.5% and 41.7% of physicians, respectively, were aged over 55 years [3].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Majority of the respondents (79.5%) were generally satisfied with their present life. The age distribution of physicians has changed substantially over the past three decades [1]. In 2010 in the United States and in 2012 in Canada, 39.5% and 41.7% of physicians, respectively, were aged over 55 years [3].…”
Section: Discussionmentioning
confidence: 99%
“…It quires the ability to make prompt decisions to deal with unexpected changes in the patient's condition [1]. Several reports have mentioned that aged practitioners, including anesthesiologists, are more likely to experience legal issues related to their practice [1,4,5]. In contrast, some studies have reported that aged surgeons did not experience increased rates of adverse events in their patients [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The population is aging and concomitantly patients present an increasing number of comorbidities. [ 1 ] For this frail population, the risk related to the surgical procedure might outweigh the benefit of the surgical intervention. [ 2 ] This restriction applies in particular for aortic valve replacement.…”
Section: Introductionmentioning
confidence: 99%